Association Between Interleukin 35 Gene Single Nucleotide Polymorphisms and the Uveitis Immune Status in a Chinese Han Population - Feng, Meng; Zhou, Shuping; Liu, Tong; Yu, Yong; Su, Qinghong; Li, Xiaofan; Zhang, Min; Xie, Xiao; Liu, Tingting; Lin, Wei (Frontiers in Immunology, 2021)
Autoimmune uveitis is characterized by immune disorders of the eyes and the whole body and is often recurrent in young adults, but its pathogenesis is still unclear. IL-35 is an essential regulatory factor in many autoimmune diseases, which is produced by Breg cells and can induce Breg cells to regulate the immune response. The relationship between the expression and gene polymorphism of IL-35 and the immune status of patients with autoimmune uveitis has not been reported. The peripheral blood of the subjects was collected from patients with Behçet’s Disease (BD) and those with Vogt–Koyanagi–Harada (VKH) syndrome. The percentage of immune cell subsets including B cells, DC, and T cells, and the expression of IL-35 in serum of these two kinds of disease were analyzed. And then, the associations between seven IL-35 single nucleotide polymorphism (SNP) sites and disease susceptibility, the immune status, the clinical characteristics, and the serum IL-35 levels were analyzed. Our results showed that the percentage of Breg cells was significantly decreased in the blood of patients with VKH syndrome compared to that of healthy controls. The levels of IL-35 in the serum of patients with VKH syndrome or BD patients were not changed significantly, compared to that of healthy controls. Furthermore, the associations between two subunits of IL-35 (IL-12p35 and EBI3) and BD or VKH patients were analyzed. We found that there was an association between the EBI3 rs428253 and the occurrence of BD. There was an association between the IL-12p35 rs2243131 and the low level of Breg cell of VKH patients. In addition, there were associations between the polymorphisms of EBI3 rs4740 and the occurrence of headache and tinnitus of VKH patients, respectively. And the genotype frequency of IL-12p35 rs2243115 was related to the concentration of serum IL-35 in patients with VKH syndrome. Thus, the specific SNP sites change of IL-35 were correlated to the immune disorders in uveitis. And they may also play a guiding role in the occurrence of clinical symptoms in patients with uveitis, especially for VKH syndrome.